2022
DOI: 10.2478/jvetres-2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of small ruminant lentiviruses originating from naturally infected sheep and goats from Poland based on the long terminal repeat sequences

Abstract: Introduction Previous gag and env sequence studies placed Polish small ruminant lentiviruses (SRLVs) isolated from sheep and goats in subtypes B1, B2, A1, A5, A12, A13, A16–A18, A23, A24 and A27. This study extended the genetic/phylogenetic analysis of previously identified Polish SRLV strains by contributing long terminal repeat (LTR) sequences. Material and Methods A total of 112 samples were analysed. Phylogenetic analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our results revealed that strains representing subtype A17 had a unique substitution of T to A in the fifth position of the TATA box. The same substitution was observed in SRLV strains belonging to subtypes A27, A20 and B3 and strains EV-1 and SAOMVV [ 29 , 35 ]. Within the group of retroviruses, there are several species that also have the same mutation in the TATA box.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our results revealed that strains representing subtype A17 had a unique substitution of T to A in the fifth position of the TATA box. The same substitution was observed in SRLV strains belonging to subtypes A27, A20 and B3 and strains EV-1 and SAOMVV [ 29 , 35 ]. Within the group of retroviruses, there are several species that also have the same mutation in the TATA box.…”
Section: Discussionsupporting
confidence: 62%
“…Sequence variations were also observed between the different HIV-1 subtypes, and several subtype-specific sequence motifs in the HIV-1 LTR region have been identified [ 26 , 27 , 28 ]. Some subtype-specific variations have also been observed for SRLVs [ 29 ]. However, it remains unclear if this subtype-specific variability in the LTR region could influence viral transcription efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors made other discordant observations, for example that the Norwegian strain 1GA belonging to group C according to Shah et al . ( 162 ) was classified as a genotype-B strain based on the gag-pol and LTR sequences ( 96 , 97 , 119 , 122 , 121 ). Comparing different fragments ( gag , env and LTR) of the same strains, Olech et al .…”
Section: Genetic Diversitymentioning
confidence: 99%
“…In addition, genotypes A, B and E contain subtypes whose sequences differ by 15-27%. According to the actual data, genotype A has twenty-seven recognized subtypes (A1-A27) [18], genotype B has five subtypes (B1-B5) [19], and genotype E has two identified subtypes (E1 и E2) [20,21].…”
Section: Introductionmentioning
confidence: 99%